Donor Dependent Variations in Hematopoietic Differentiation among Embryonic and Induced Pluripotent Stem Cell Lines. - Olivier Féraud; Yannick Valogne; Michael W Melkus; Yanyan Zhang; Noufissa Oudrhiri; Rima Haddad; Aurélie Daury; Corinne Rocher; Aniya Larbi; Philippe Duquesnoy; Dominique Divers; Emilie Gobbo; et al. (PLoS ONE, 2016)
Hematopoiesis generated from human embryonic stem cells (ES) and induced pluripotent stem cells (iPS) are unprecedented resources for cell therapy. We compared hematopoietic differentiation potentials from ES and iPS cell lines originated from various donors and derived them using integrative and non-integrative vectors. Significant differences in differentiation toward hematopoietic lineage were observed among ES and iPS. The ability of engraftment of iPS or ES-derived cells in NOG mice varied among the lines with low levels of chimerism. iPS generated from ES cell-derived mesenchymal stem cells (MSC) reproduce a similar hematopoietic outcome compared to their parental ES cell line. We were not able to identify any specific hematopoietic transcription factors that allow to distinguish between good versus poor hematopoiesis in undifferentiated ES or iPS cell lines. There is a relatively unpredictable variation in hematopoietic differentiation between ES and iPS cell lines that could not be predicted based on phenotype or gene expression of the undifferentiated cells. These results demonstrate the influence of genetic background in variation of hematopoietic potential rather than the reprogramming process.